2015
DOI: 10.7763/ijesd.2015.v6.722
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for Fenton Process in Removal of COD for Landfill Leachate Treatment

Abstract: Abstract-Present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Deng 34 (240 mM; CODo=1100-1300 mg L -1 ) and Wu et al 40 (240 mM; CODo=5780 mg L -1 ), higher than those found by Lopez et al 37 (97 mM; CODo=10540 mgL -1 ) and Santin-Gusman et al 57 (9,17 mM; CODo=2296 mg L -1 ) and lower than Moravia et al 48 (470 mM; CODo=2834 mg L -1 ) and Badawy et al 39 (653mM; CODo=13650 mg L -1 ).…”
Section: The Point Of Saturation Obtained In This Work Is Close To Thmentioning
confidence: 60%
See 1 more Smart Citation
“…Deng 34 (240 mM; CODo=1100-1300 mg L -1 ) and Wu et al 40 (240 mM; CODo=5780 mg L -1 ), higher than those found by Lopez et al 37 (97 mM; CODo=10540 mgL -1 ) and Santin-Gusman et al 57 (9,17 mM; CODo=2296 mg L -1 ) and lower than Moravia et al 48 (470 mM; CODo=2834 mg L -1 ) and Badawy et al 39 (653mM; CODo=13650 mg L -1 ).…”
Section: The Point Of Saturation Obtained In This Work Is Close To Thmentioning
confidence: 60%
“…Mostly, the results were obtained by factors analysis separately, one-factor-at-a-time, and hence do not consider the interaction between them. Only in the last decade was it possible to observe the application of factorial analysis 31,38,40,45,46,48,49,53,54,55,56,57,58,59 .…”
mentioning
confidence: 99%
“…The compound commonly used in several studies as a supplier of ferrous ions (Fe 2+ ) for the Fenton process is ferrous sulfate heptahydrate (FeSO 4 •7H 2 O) [46][47][48].…”
Section: Fementioning
confidence: 99%
“…An increase in the H 2 O 2 dose results in better effects of the contaminant oxidation process, but too high a dose of H 2 O 2 in relation to the substrate may cause the • OH radical binding by H 2 O 2 . Hydrogen peroxide is harmful to many organisms, which is of significance if the Fenton process is carried out prior to biological treatment [12,17,18]. The unused portion of hydrogen peroxide results in an overvaluation of the COD being determined (in a reaction with strong oxidants e.g.…”
Section: Introductionmentioning
confidence: 99%